FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN KUNJUNGAN ANTENATAL CARE PADA MASA PANDEMI DI WILAYAH KERJA PUSKESMAS SEI LANGKAI - Cahyati, Yuliza; Susanti, Susanti (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
In the Batam City Health Office data, it can be seen that the data on visits by pregnant women is mostly in the working area of the Sei Langkai Health Center, namely 3,910 pregnant women with a coverage of the First Visit (K1) of 99.8% and the coverage of Repeat Visits (K4) of 93.8% it can be seen that repeat visits (K4) decreased by 6% (Puskesmas Sei Langkai, 2019). While the smallest visit for pregnant women was at the Kabil Health Center, which was 742 pregnant women with a coverage of the First Visit (K1) of 97.8% and the coverage of Repeat Visits (K4) of 94.6% there it was seen that the Repeat Visit (K4) decreased by 3 ,2%. Knowledge is the result of knowing, and this occurs after people have sensed certain objects. Anxiety is tension, insecurity and worry that arises because it is felt that something unpleasant is happening but its source is largely unknown and comes from within. Husband's support is an encouragement, motivation for his wife both morally and materially. Husband's support can serve as a preventive strategy to reduce stress and its negative consequences. The research design is an analytical survey with a cross sectional approach. The population is 275 pregnant women, with accidental sampling technique. The research time was September 2020, the research instrument used a questionnaire. Data analysis used chi square statistical test. The results showed that some of them had good knowledge (76.7%) and were obedient (23.3%), some mothers experienced mild anxiety (80%) and were not anxious (20%), some husband's support was supportive (86.7%). and did not support (13.3%), adherence to antenatal care visits was partially compliant (73.3) and non-adherent (26.7%). There is a relationship between knowledge and compliance with pregnant women (p value = 0.006), there is a relationship between maternal anxiety and compliance with pregnant women (p value = 0.027), there is a relationship between husband's support and compliance with pregnant women (p value = 0.048%). The researcher concludes that there is a relationship between knowledge, mother's anxiety, husband's support and compliance with antenatal care visits at the Sei Langkai Health Center Batam City in 2020. Suggestions for pregnant women to increase knowledge about pregnancy by routinely carrying out pregnancy checks or seeking information through various other media.